Relationship between the privacy index and the speech privacy class - Müller-Trapet, Markus; Gover, Bradford N (The Journal of the Acoustical Society of America, 2019)
It is regularly debated which metric to use for the assessment of architectural speech privacy. For open-plan offices, the Privacy Index, derived from the Articulation Index according to ASTM E1130 (2016), is usually used. For closed offices, the Speech Privacy Class is determined according to ASTM E2638 (2010). Disregarding the measurement method, and the fact that the metrics show different behavior regarding the Signal-to-Noise Ratio, both metrics are directly related and values of the Speech Privacy Class can thus be converted to Privacy Index values. The relationship is demonstrated and the result is validated with field and laboratory measurement data.